Pengaruh Energi Terhadap Pengiriman Data Pada Protokol Fisheye State Routing (FSR) Dalam Mobile Ad Hoc Network (Manet) - Dahru Wildan Pradanaputra; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The energy level owned by a node will affect the services performed by that node. When the node's energy is at a high level, the node will provide communication services for sending data and routing, but when the node's energy is at a low level the services performed by that node will be limited. The limit given to the node is when the remaining node energy is below 20% of the initial energy, the node will discard all packets that will be forwarded and when the node's energy sis has entered below 10%, the node will discard all packets that will be forwarded and do not do routing. The application of these energy restrictions results in changes in the Quality of Service. The testing of the application of energy restriction is carried out using a number of diverse nodes, namely 30, 40, and 50. The results are taken with two tests, the first test without applying energy restriction and the second test uses energy restriction. The results of the comparison of the average throughput test value for the number of nodes 30 and 50 have increased, but for testing with 40 nodes has decreased in value. The results of the comparison of packet delivery ratio testing values ​​on all tests the number of nodes has decreased. And the results of testing the remaining energy changes the value of the remaining energy owned by each node.